La cooperacion : ¿un instrumento de refuerzo del soft power? (2009)
The concept of the existence of the Soft Power, developed by Joseph Nye, and which is based upon the that deepen the power of a State, may be identified today with other actors of organizations. The dynamics of the internationalcooperation,withintheseorganizations, seem to accompany the existence of this type of power. And it is in this way that the phenomenon of the Francophonie has turned out to be a breeding ground for the study of a model of Soft Power which is exerted in the institutional level within organizations like the International Organization of la Francophonie – OIF – and in relation to the United Nations Organizations – UNO – and its operators like UNESCO, and in the bilateral level between States, for example, in the of bilateral cooperation between France and Colombia. In order to verify such a statement, this research shows both a quantitative and qualitative reading of the actions which make evident the existence of such a type of power which turns out to be essential.